2019
DOI: 10.1111/jfbc.12834
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive effects of protein derivatives from Mucuna pruriens on a streptozotocin‐induced type 1 diabetes murine model

Abstract: Type 1 diabetes is an autoimmune disease induced by abnormal insulin secretions from β‐cells in pancreas. The present study aimed to investigate the immunosuppressive effects from protein derivatives of Mucuna pruriens on a murine model of Type 1 diabetes. Hydrolyzate and five peptide fractions with different molecular weight were administered orally by 14 days, followed T1D murine model was built by intraperitoneal injection of streptozotocin over 5 days. The mice weight, blood glucose levels, anti‐insulin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The protein hydrolysate was submitted to ultrafiltration process using the protocol of Laviada-Castillo et al (2019). Protein hydrolysate was passed through ultrafiltration membranes with molecular weight cut-off (MWCO) of 1, 3, 5 and 10 kDa using a stirred ultrafiltration system.…”
Section: Isolation Of Peptide Fractionsmentioning
confidence: 99%
“…The protein hydrolysate was submitted to ultrafiltration process using the protocol of Laviada-Castillo et al (2019). Protein hydrolysate was passed through ultrafiltration membranes with molecular weight cut-off (MWCO) of 1, 3, 5 and 10 kDa using a stirred ultrafiltration system.…”
Section: Isolation Of Peptide Fractionsmentioning
confidence: 99%
“…In addition, the seeds of M. pruriens contain various kinds of phytochemical substances, such as carbohydrates and amino acids, as well as anti-nutrient substances, such as polyphenols, phytates, tannins, and saponins [14,15]. Many biological studies have reported that M. pruriens possesses anti-Parkinson [16], antidiabetic [17], antioxidant [18,19], and antibacterial activities [20], as well as male fertility and aphrodisiac effects [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolysed seeds of Mucuna pruriens contains (20–35%) protein and peptides, for example, F5‐10 KDa peptide fraction inhibits NO and H 2 O 2 production and reduces IL‐6 and TNF‐α inflammatory markers in macrophages of Balb/c mice (Leo, Argáez, Fernández, Puc, & Campos, 2018). Recently, Laviada‐Castillo et al, have also confirmed the immunosuppressive and antiinflammatory effects of Mucuna pruriens in an animal model of streptozotocin‐induced type‐1 diabetes (Laviada‐Castillo et al, 2019). Quinoa crude polysaccharides (QPS) isolated from Chenopodium quinoa is reported to enhance immune functions in ICR mice by inducing phagocytic activity of mononuclear macrophages and improves IFN‐γ, IL‐6, IFN‐α, IgM expression in serum (Fan, Li, & Bai, 2019).…”
Section: Plants As Biological Sources For Immunomodulatorsmentioning
confidence: 86%